Global Supply Chains, Standards and the Poor: How the Globalization of Food Systems and Standards Affects Rural Development and Poverty - Swinnen, Johan F.M (CABI, 2014)
The past decade has witnessed an effective globalization of supply chains and an unprecedented increase in foreign investment in agricultural commodities and food markets worldwide, the rise of food quality and safety standards in the rich countries and the spread of these standards – often set by private companies – to developing and transition countries and a dramatic growth in high-value food exports from developing countries. One of the most striking features of these developments has been the dramatic rise of investments by global retail chains (‘supermarkets’) in emerging, transition and developing countries. Most recently, Russia, China and India were the top three destinations of foreign investment flows by multinational retail companies